2015
DOI: 10.1039/c5ra15301h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interaction of inorganic mercury(ii) with catalase: a spectroscopic study in combination with molecular docking

Abstract: Interaction of inorganic mercury(ii) with catalase was investigated using spectroscopic methods. Moreover, molecular docking was used to distinguish the interactions between different species of inorganic mercury(ii) and catalase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Because the RC has a relatively large surface, a large number of deep voids and variable electrostatic surface profile, plenty of places for the Hg 2+ ions to bind are assured. This is shown in the 3D movie attached to the electronic version of the MS. For comparison with other proteins, even the weak binding constants of mercury(II) to bacterial RC are much larger than those to other proteins such as catalase (Chen et al 2015) or bovine serum albumin (Chunmei et al 2014). From the large number of binding sites and relatively high binding affinities, one can conclude that the RC serves as sponge for mercury(II) ions.…”
Section: Discussionmentioning
confidence: 98%
“…Because the RC has a relatively large surface, a large number of deep voids and variable electrostatic surface profile, plenty of places for the Hg 2+ ions to bind are assured. This is shown in the 3D movie attached to the electronic version of the MS. For comparison with other proteins, even the weak binding constants of mercury(II) to bacterial RC are much larger than those to other proteins such as catalase (Chen et al 2015) or bovine serum albumin (Chunmei et al 2014). From the large number of binding sites and relatively high binding affinities, one can conclude that the RC serves as sponge for mercury(II) ions.…”
Section: Discussionmentioning
confidence: 98%
“…The modified double-logarithm form of the Stern-Volmer equation helps in determining the binding parameters for a quencher-fluorophore interaction [25]. The modified equation is written as 1.…”
Section: Spectral Analysis Of L-cys-capped Gqdsmentioning
confidence: 99%
“…Long-term exposure of Cr 6+ increases the substrate levels (superoxide radicals) of SOD, whereas SOD activity decreased with the increase in its substrate levels in this study, indicating that antioxidant defense probably has been impaired in sea cucumbers. In terms of CAT, as an important enzymatic scavenger (Chen et al, 2015), removing the H 2 O 2 by catalyzing its decomposition. The present study found that significantly lower CAT activities were found in groups 100 and 200 mg/kg than those in control group.…”
Section: Immunity Responsesmentioning
confidence: 99%